2014
DOI: 10.1371/journal.pone.0087506
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course Changes of Oxidative Stress Response to High-Intensity Discontinuous Training versus Moderate-Intensity Continuous Training in Masters Runners

Abstract: Beneficial systemic effects of regular physical exercise have been demonstrated to reduce risks of a number of age-related disorders. Antioxidant capacity adaptations are amongst these fundamental changes in response to exercise training. However, it has been claimed that acute physical exercise performed at high intensity (>60% of maximal oxygen uptake) may result in oxidative stress, due to reactive oxygen species being generated excessively by enhanced oxygen consumption. The aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 58 publications
8
55
1
1
Order By: Relevance
“…Different training methods and different assessment parameters as well as different groups of subjects were involved may contribute to the inconsistent findings in the present study. In this study, improved sperm DNA integrity after HIIT intervention are consistent with Vezzoli and coworkers who investigated the effect of 8 weeks of high-intensity discontinuous training (at 120-140% VO 2peak ) on 8-hydroxy-2-deoxyguanosine (8-OH-dG) as a biomarker of DNA base modifications in long-distance runners and showed a decrease (∼25%) in urinary 8-OH-dG excretion after exercise (Vezzoli et al 2014). These findings may be influenced by increases in endogenous antioxidant status, upregulation of antioxidant capacity, increase in radical scavenging capacity of spermatozoa or seminal plasma as well as upregulation in DNA damagerepairing enzymes after participation in HICT and HIIT interventions.…”
Section: Discussionsupporting
confidence: 89%
“…Different training methods and different assessment parameters as well as different groups of subjects were involved may contribute to the inconsistent findings in the present study. In this study, improved sperm DNA integrity after HIIT intervention are consistent with Vezzoli and coworkers who investigated the effect of 8 weeks of high-intensity discontinuous training (at 120-140% VO 2peak ) on 8-hydroxy-2-deoxyguanosine (8-OH-dG) as a biomarker of DNA base modifications in long-distance runners and showed a decrease (∼25%) in urinary 8-OH-dG excretion after exercise (Vezzoli et al 2014). These findings may be influenced by increases in endogenous antioxidant status, upregulation of antioxidant capacity, increase in radical scavenging capacity of spermatozoa or seminal plasma as well as upregulation in DNA damagerepairing enzymes after participation in HICT and HIIT interventions.…”
Section: Discussionsupporting
confidence: 89%
“…This was also contrary to the results of the studies in which interval training programs were evaluated as significant increases in GPx, catalase (CAT) and total antioxidant capacity (TAC) were obtained following three weeks of HIIT program (Bogdanis, et al, 2013). On the other hand, no significant change in CAT, SOD and GPx was found after a HIIT program consisting of only three all-out sprint cycling sessions (Fisher, et al, 2011) as well as in resting TAC following four and eight weeks of HIIT (Vezzoli, et al, 2014). Also, no significant change in GPx, GR and SOD following six weeks of training was reported in the only study that investigated the effects of RST on muscle antioxidant enzymes (Hellsten, et al, 1996).…”
Section: Discussioncontrasting
confidence: 62%
“…Bogdanis et al (2013) reported a significant reduction of protein carbonyls (PC) and a non-significant decrease of thiobarbituric acid reactive substances (TBARS) following three weeks of sprint interval training consisting of four to six 30-second all out sprints. A significant reduction of TBARS, but not of PC, was also reported following eight weeks of HIIT consisting of eighteen 1-minute intervals performed at 120 to 140% of VO 2peak and separated by 2-minute rest intervals performed at 65% VO 2peak in master runners (Vezzoli, et al, 2014). Finally, after only three HIIT sessions consisting of four 30-second cycling sprints performed at 90% of maximal anaerobic power and separated by 4-minute active rest intervals, Fisher et al (2011) reported a reduced acute response of TBARS following the session, indicating a reduction of oxidative stress as a result of even such a short training period.…”
Section: Discussionmentioning
confidence: 68%
“…SPW training is one of the most effective interventions for the maintenance/increase of muscle mass, which has long been related to a reduction in chronic inflammatory status due to the secretion of anti-inflammatory myokines [45]. On the other hand, the negative association between redox balance and weekly hours of aerobic training is somewhat inconclusive, because there is evidence showing that aerobic exercise reduces oxidative stress [46][47][48]. We believe that, in general, master athletes have a good redox balance, but those athletes with a higher volume of aerobic training elicit a greater oxidative stress.…”
Section: Discussionmentioning
confidence: 99%